Manajemen Strategik dengan Orientasi Pasar dan Orientasi Belajar pada Kinerja Inovasi Rumah Batik Bahalap - Ina Karuehni; Peridawaty Peridawaty (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
Research within the field of small business strategic management for business management and strategy at the Bahalap batik house in Central Kalimantan. The importance of market support and learning skills. The aims of this analysis are to enhance the performance of small businesses with strategic management that supports the variables that support the market and to find out lessons to improve positive leads to small businesses within the Bahalap batik house, by supporting the market must produce merchandise that matches the requirements of customers. analysis ways with structured interviews and quantitative questionnaires victimization SPSS 24.0, on 50 customers. The implications of strategic management analysis are necessary for small businesses to urge innovation support. Encouragement of the business unit's ability of market objectives and learning objectives within the business atmosphere as a business strategy and to realize the vision goals, the mission of tiny businesses Increasing small businesses to support small businesses through strategic management will facilitate alternative analysis to develop strategic management.